2013
DOI: 10.1016/j.juro.2012.08.255
|View full text |Cite
|
Sign up to set email alerts
|

Readability Assessment of Online Urology Patient Education Materials

Abstract: Urological online patient education materials are written above the recommended reading level. They may need to be simplified to facilitate better patient understanding of urological topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 18 publications
11
74
1
3
Order By: Relevance
“…Consistent with the results of previous English and German PEM readability assessments [11][12][13]16], only 13.8% (12/87 assessments; Table. 2) met the NIH readability recommendations of a 7th-8th grade reading level [15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with the results of previous English and German PEM readability assessments [11][12][13]16], only 13.8% (12/87 assessments; Table. 2) met the NIH readability recommendations of a 7th-8th grade reading level [15].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have investigated the readability of PEM in different fields of medicine [9,10]. Urological [11,12] and non-urological [13] trials concluded that the readability of English written information material was more difficult than the level of difficulty recommended by the American Medical Association [14] and National Institutes of Health (NIH) [15]. A similar conclusion was drawn for German-language hospital websites of surgical and ear, nose and throat departments, which addresses a target audience of over 100 million German native speakers [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Colaco et al analyzed the readability of online patient education materials from the American Urological Association and from 17 academic urology departments located in the northeastern U.S. 13 Their results were similar to our own. None of the online resources demonstrated mean readability levels consistent with guideline recommendations and most required at least a university level education in order to interpret.…”
Section: Readability Of Patient Information Materialssupporting
confidence: 83%
“…5,11 Despite these guidelines, many of the Web sites of several national physician organizations, including medical, surgical, and subspecialty fields, have provided texts at a level too complex for most of the public to comprehend. [12][13][14][15][16][17][18][19][20][21][22][23] Recent reports that evaluate the readability of patient education resources on radiology Web sites, sponsored by major organizations such as the Radiological Society of North America, the American College of Radiology, the Society of Interventional Radiology, and the Cardiovascular and Interventional Radiologic Society of Europe, demonstrated that the material offered to the public is written at a level well above the AMA and the National Institutes of Health recommendations. 24,25 In this study, we investigated the level of readability of all patient education resources on the American Society of Neuroradiology (ASNR) Web site by using a variety of quantitative readability-assessment scales.…”
mentioning
confidence: 99%